2018
DOI: 10.1016/j.biomaterials.2018.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Overhang molecular beacons encapsulated in tethered cationic lipoplex nanoparticles for detection of single-point mutation in extracellular vesicle-associated RNAs

Abstract: Detection of specific extracellular RNAs has been developed for non-invasive cancer diagnosis. However, accurate and efficient identification of RNAs with single-point mutation in cancer cells-derived extracellular vesicles (EVs) is challenging. Herein, we present a unique overhang molecular beacon with internal dye (Ohi-MB) with a stable hairpin structure, fast hybridization kinetics and single mismatch specificity. Ohi-MBs are encapsulated in cationic lipoplex nanoparticles (CLNs) that are tethered on a gold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…It has been suggested that tethered cationic lipoplex nanoparticle (tCLN) biochip combined with total internal reflection fluorescence (TRIF) microscopy is an approach which can specifically quantify RNA in exosomes . Therefore, in this study, this method had been employed to demonstrate whether gRNA was present in the cell‐derived exosomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that tethered cationic lipoplex nanoparticle (tCLN) biochip combined with total internal reflection fluorescence (TRIF) microscopy is an approach which can specifically quantify RNA in exosomes . Therefore, in this study, this method had been employed to demonstrate whether gRNA was present in the cell‐derived exosomes.…”
Section: Resultsmentioning
confidence: 99%
“…tCLN : The detection of exosomal RNA using tCLNs was previously described . Briefly, to make tCLN biochips, a thin Au layer (15 nm) was deposited on a glass cover slip using a Denton e‐beam evaporator (DV‐502A, Denton Vacuum, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…When serum is applied to the biochip, the molecular beacons recognize target miRs in exosomes, and the interaction is read by a total internal reflection fluorescence microscope (15). The copy numbers of the exmiRs can then be obtained by the fluorescence signals of the molecular beacons (MBs) (15). Wu et al (13) demonstrated that the levels of exmiRs detected by the TCLN biochip were consistent with the widely used reverse transcription-quantitative PCR (RT-qPCR) method.…”
Section: Introductionmentioning
confidence: 94%
“…Molecular beacons in liposome nanoparticles serve as molecular probes for target miRs. When serum is applied to the biochip, the molecular beacons recognize target miRs in exosomes, and the interaction is read by a total internal reflection fluorescence microscope (15). The copy numbers of the exmiRs can then be obtained by the fluorescence signals of the molecular beacons (MBs) (15).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc transporter ZIP4 [ 37 ], cytoskeleton-associated protein 4, a novel Dickkopf1 receptor [ 96 ], and annexin A1 [ 200 ] are also potential biomarkers. A panel of miRNAs, mRNAs, and proteins derived from EVs is useful for the early diagnosis of pancreatic cancer [ 201 , 202 , 203 , 204 , 205 , 206 , 207 ]. It may be possible to predict treatment outcomes using EVs [ 208 ].…”
Section: Potential Of Evs For Liquid Biopsymentioning
confidence: 99%